Perkembangan Kelembagaan Dari Negeri Dan Marga Menjadi Desa Di Kecamatan Tungkal Ulu Kabupaten Tanjab Barat Provinsi Jambi - Erdianto ' (Jurnal Ilmu Hukum, 2010)
Reveals the historical development of the village or clannamed country means also discuss the history of thelaw on setting up an autonomous region in the small-est administrative structure Indonesia. This paper con-cluded a few things about the growth and develop-ment of villages in the District of West Tanjab TungkalUlu Jambi Province. Adjustment system according tothe form of the village who live in actual Java stuntcapability for autonomous villages.